Lesia Ukrainka's Epistolary Idiolect in the Interior of Family Communication: Ulita (Linguostylistic Studies, 2020)
The article highlights one of the dominant features of Lesya Ukrainka's epistolary idiolect in the context of family communication, which is manifested primarily in the presence of occasional names in the active vocabulary of each member of this family and which serve markers of lexical regulations, characteristic of this family sociolect. On the example of one of such lexical innovations functioning - Ulita, the peculiarities of its origin and motivation in the Kosach family communication have been established (Olga Petrovna Kosach (Olena Pchilka), mother of Lesya Ukrainka, was probably involved in its creation). The study argues that this lexeme is most actively used in the thematic plane of epistolary communication, usually connected with the literary works of the family members. Lesya Ukrainka uses it as a nomination of her own works (first regarding those that are created slowly, then – any work (newly created, old, handwritten, or printed). Quite often, it concerns a separate text variety, most frequently, a piece of poetry. The most frequent fixations of this token we observe in the epistolary texts of Lesya Ukrainka and Mykhailo Kosach. The study has revealed a number of productively used derivatives (mostly adjectives and verbs), in particular ulitnyi, ulitiachyi, ulityty, zaulichuvatysia, rozulitytysia and more. An important feature of their functioning in the idiolect of both communicants is their high degree of compatibility, especially the token ulitay, the use of the author's individual derivatives, such as naulicheno, ulityna, ulitynnia, etc. The available graphic markers for the lexemes ulita and ulitnyi in the letters of Lesya Ukrainka and Mykhailo Kosach most probably demonstrate the intertextual status of these tokens and their borrowing from the mother's idiolect, as all other derived tokens of this word-forming series are devoid of such distinction. The active use of such lexical innovations in the epistolary interpersonal communication of the family should be considered as a manifestation of language play within a confined space, partly - a kind of creative entertainment for each of the communicators, a means of stylistic expression of their idiolect, but in no way a manifestation of infantilism or compulsion, initiated by their mother, Olena Pchilka.
Keywords: epistolary text; family communication; lexical regulation; occasionalisms